2021
DOI: 10.1007/s11557-021-01669-w
|View full text |Cite
|
Sign up to set email alerts
|

Quo vadis? Historical distribution and impact of climate change on the worldwide distribution of the Australasian fungus Clathrus archeri (Phallales, Basidiomycota)

Abstract: Clathrus archeri is a fungus native to Australia and New Zealand that has started to expand into Europe, and it is considered a potentially invasive species. In this study, we examine the historical occurrence, current geographical range and potential future changes in the distribution of C. archeri using worldwide distribution data. Ecological modelling was used to assess the locations of the potential climatic niches of C. archeri within both its native and introduced ranges in the past, present and future. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…Similar results, highlighting that climatic conditions (precipitation and mean temperature) are important predictors driving the occurrence of C. archeri fruitbodies, have been published for Poland (Pietras et al 2016). The results of this study are in agreement with those published in Pietras et al (2021), who presented a global assessment of both the potential suitable habitats and the limiting factors for C. archeri. Their comprehensive analysis underlined the importance of climatic conditions, as well as the presence of highly suitable regions in Central Europe and the Carpathian Mountains, for the expansion of the species.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results, highlighting that climatic conditions (precipitation and mean temperature) are important predictors driving the occurrence of C. archeri fruitbodies, have been published for Poland (Pietras et al 2016). The results of this study are in agreement with those published in Pietras et al (2021), who presented a global assessment of both the potential suitable habitats and the limiting factors for C. archeri. Their comprehensive analysis underlined the importance of climatic conditions, as well as the presence of highly suitable regions in Central Europe and the Carpathian Mountains, for the expansion of the species.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, the distribution pattern of L. tomentosus in Australia and New Zealand is similar to the known biogeography of alien russuloid fungi (Cooper et al 2022) and the previously reported saprotrophic fungus Clathrus archeri (Pietras et al 2021) or the ectomycorrhizal Rhizopogon pseudoroseolus (Pietras 2019).…”
Section: Distributionsupporting
confidence: 83%
“…Invasions of plants and pathogens are typically related to development, trade, and tourism (Levine and D'Antonio 2003). Nonnative symbiotic fungi are frequently associated with touristic places such as trails, camping sites, and botanical gardens (Pietras et al 2018(Pietras et al , 2021Pietras 2019). Especially in highly urbanized places, plenty of nonnative ectomycorrhizal trees seem to be perfectly suited for alien symbiotic fungi.…”
Section: Human Vectormentioning
confidence: 99%
“…We considered this cautiously 63 since soil properties result from the local substrate, climate, and vegetation and greatly depend on the composition of local microbiota 64 . Numerous studies showed that climate will also affect these organisms 65 , 66 . Thus, predicting future soil characteristics changes is extremely difficult.…”
Section: Methodsmentioning
confidence: 99%